A study on the convergence of lean and green management goals - Larinina Tatyana; Djoldosheva Tamara; Mottaeva Asiiat (BIO Web of Conferences)
Goal setting determines the transformation of production management methods and approaches. Real practice often differentiates Lean and Green approaches. At first glance, the indicators and metrics are so different that there is a feeling of the need to build the company’s organizational structure accordingly, allocate different budgets and implement different activities. This is largely due to the different standards and rules governing these approaches. The study examines the hypothesis that the goals of Lean and Green Management are convergent at the current stage of development. Understanding the possibility and even the need (in accordance with the Lean approach) to combine and minimize resources will increase the efficiency of manufacturing enterprises. The study showed that, despite the initial apparent difference of Lean and Green management goals, in fact, at least two of the three stated goals are convergent: 1) goals aimed at reducing resource consumption and 2) goals aimed at ensuring the growth of enterprise performance indicators. The third group of goals aimed at forming a conscious “lean” attitude of personnel to work, equipment, and the environment, apparently implies different understandings and interpretations. This may probably be due to the fact that Lean management operates more with material resources, while Green management is aimed at energy resources and the environment.